2018
DOI: 10.3324/haematol.2018.194894
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-free remission after two-year consolidation therapy with nilotinib in patients with chronic myeloid leukemia: STAT2 trial in Japan

Abstract: The purpose of this trial was to evaluate the efficacy of 2-year consolidation therapy with nilotinib, at a dose of 300 mg twice daily, for achieving treatment-free remission in chronic myeloid leukemia patients with a deep molecular response (BCR-ABL1IS ≤0.0032%). Successful treatment-free remission was defined as no confirmed loss of deep molecular response. We recruited 96 Japanese patients, of whom 78 sustained a deep molecular response during the consolidation phase and were therefore eligible to disconti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 27 publications
1
81
1
3
Order By: Relevance
“…In our cohort of patients, the TFR rate was higher than the one currently reported in the IM and second‐generation TKI discontinuation studies but, as expected, the loss of MR occurred in 24/111 (22%) cases early after TKIs discontinuation (3 months). This highly positive selection could be explained, as above reported, by the prolonged treatment and the DMR duration . Furthermore, the major part of the patients (75%) who underwent TKIs discontinuation was characterized by the presence of the transcript b3a2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our cohort of patients, the TFR rate was higher than the one currently reported in the IM and second‐generation TKI discontinuation studies but, as expected, the loss of MR occurred in 24/111 (22%) cases early after TKIs discontinuation (3 months). This highly positive selection could be explained, as above reported, by the prolonged treatment and the DMR duration . Furthermore, the major part of the patients (75%) who underwent TKIs discontinuation was characterized by the presence of the transcript b3a2.…”
Section: Discussionmentioning
confidence: 99%
“…This highly positive selection could be explained, as above reported, by the prolonged treatment and the DMR duration. 30,31 Furthermore, the major part of the patients (75%) who underwent TKIs discontinuation was characterized by the presence of the transcript b3a2. This transcript has been recently associated with a better response to the TKIs treatment, resulting in higher sustained DMR rate, 39 and a longer TFR.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of nonoptimal response, the change from a TKI to another TKI is optional, if it is believed that it may help to achieve a deeper molecular response and to bring the patient to TFR. There are some data, 20,26,32,43 and there is some experience, of switching from imatinib to a 2GTKI, not from a 2GTKI to another TKI. All studies suggest that such a switch may increase the rate of deep molecular response (DMR), hence the number of patients eligible for treatment discontinuation and TFR, but, regrettably, all of these studies are single-arm and do not allow for calculation of the benefit of a switching policy against the risk of increased toxicity.…”
Section: The Switch From First-linementioning
confidence: 99%
“…Many studies, some retrospective and some prospective, have shown beyond any doubt that a consistent proportion, ranging between 30% and 70%, of the patients who discontinue treatment after having achieved a DMR (MR 4.0, BCR-ABL1 #0.01% IS , or MR 4.5, BCR-ABL1 #0.0032% IS ) may remain treatment-free for an as-yet undefined period of time. [36][37][38][39][40][41][42][43][44][45][46][47][48] It is important to underline that the patients with molecular relapse after discontinuation do not progress, and are almost all able to achieve DMR again upon retreatment, and that some of them can become eligible for a second attempt of treatment discontinuation. The probability of achieving TFR may depend on several factors: leukemia or patient characteristics, TKI type, treatment duration, DMR duration, etc.…”
Section: Treatment Discontinuation and Tfrmentioning
confidence: 99%
See 1 more Smart Citation